System analysis and modeling : technology-specific aspects of models : 9th International Conference, SAM 2016, Saint-Malo, France, October 3-4, 2016. Proceedings /: technology-specific aspects of models : 9th International Conference, SAM 2016, Saint-Malo, France, October 3-4, 2016. Proceedings. (2016) - Unknown
No abstract available